1985
DOI: 10.1073/pnas.82.20.7145
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellin: a quantifiable marker for Purkinje cell maturation.

Abstract: The cerebellum-specific hexadecapeptide cerebellin has been localized by immunocytochemical means to the perikarya and dendrites of cerebellar Purkinje cells. Biochemical analysis using ion-pairing HPLC shows cerebellin to first appear 5 days after birth, whereafter levels rise to a maximum at 25 days postpartum, and then decline to stable adult values. This same pattern of development occurs with a lag of approximately 5 days for the major metabolite of cerebellin, des-Serl-cerebellin. The immunocytochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 13 publications
3
61
1
Order By: Relevance
“…Another Purkinje cell marker peptide, cerebellin, shows a similar time course of appearance but decreases in concentration after day 25 postpartum until a stable adult level is attained (11). PEP-19 does not exhibit this characteristic decline in concentration (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another Purkinje cell marker peptide, cerebellin, shows a similar time course of appearance but decreases in concentration after day 25 postpartum until a stable adult level is attained (11). PEP-19 does not exhibit this characteristic decline in concentration (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Precise details of the production and characterization of the anti-PEP-19 antisera will be described elsewhere. Briefly, a peptide was synthesized corresponding to residues 43-55 of PEP-19 and coupled to bovine thyroglobulin as described (11). This region of PEP-19 has no tTo whom reprint requests should be addressed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cbln1⌬21N and Cbln3⌬24N are the secreted mature forms of Cbln1 and Cbln3, respectively. Cbln1⌬54N is the product generated by cleavage at a putative tumor necrosis factor (TNF) alpha-cleaving enzyme-like site in Cbln1 responsible for liberating the peptide, cerebellin (1,33,34,40), and Cbln3⌬57N is the equivalent fragment in Cbln3. Cbln1⌬61N and Cbln3⌬63N constitute just the C1q domains of the two family members.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, it was suggested that the N-terminal truncated version of CER, des-Ser1-CER, is an apparent metabolite of CER. However, recent data failed to confirm this contention (1,34,36,37). In regards to the adrenal gland, both CER and desCER exert a modulatory effect on corticosteroid secretion (25,(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 78%